THE EFFECT OF SUPERVISION IMPLEMENTATION TOWARDS TEACHER PERFORMANCE AT SMKN BUSINESS MANAGEMENT GROUP IN PADANG CITY - Ermita, Ermita (Universitas Pendidikan Indonesia, 2017)
Abstract-This research aimed to obtain information on: Performance of teachers, Implementation of supervision and significant influence between the implementation of the supervision to the teachers performance at SMKN Business and Management in Padang. The hypothesis of this research is the implementation of academic supervision significantly affect to the teachers performance. The population this research are 125 people all of teachers. Samples 76 people were taken using Random Sampling. Instrument of researchusing questionnaire with Likert scale models that have been tested for validity and reliability. Data were analyzed using correlation and simple regression techniques with the help of statistical program SPSS version 20.0 IBMM. The results showed that: the performance of teachers enough category in the level of achievement of 71.49%. Implementation of supervision by the principal enough category in the level of achievement of 69.14% and Implementation of supervision by the principal positive effect on the performance of teachers at SMK Business and Management Group in Padang City of 9.3%. Keywords-The Implementation of Supervision and Teachers Performance